2021
DOI: 10.1021/acs.jmedchem.1c00419
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Redox-Sensitive Spermine Prodrug for the Potential Treatment of Snyder Robinson Syndrome

Abstract: Snyder Robinson Syndrome (SRS) is a rare disease associated with a defective spermine synthase gene and low intracellular spermine levels. In this study, a spermine replacement therapy was developed using a spermine prodrug that enters cells via the polyamine transport system. The prodrug was comprised of three components: a redox-sensitive quinone “trigger”, a “trimethyl lock (TML)” aryl “release mechanism”, and spermine. The presence of spermine in the design facilitated uptake by the polyamine transport sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The results showed that the spermine level was significantly increased in cells overexpressing SMS, while after knocking down SMS, the spermidine level was significantly accumulated ( Figures 3A, B ). It is noteworthy that similar results of spermidine buildup have been seen in the fibroblasts of patients with Snyder Robinson Syndrome which have defective SMS ( 29 ). To further verify the relationship between SMS and AKT , western blot analysis was performed and showed that over-expression of SMS can up-regulate the level of p-AKT while knocking down SMS can reduce the expression of p-AKT ( Figure 3C ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The results showed that the spermine level was significantly increased in cells overexpressing SMS, while after knocking down SMS, the spermidine level was significantly accumulated ( Figures 3A, B ). It is noteworthy that similar results of spermidine buildup have been seen in the fibroblasts of patients with Snyder Robinson Syndrome which have defective SMS ( 29 ). To further verify the relationship between SMS and AKT , western blot analysis was performed and showed that over-expression of SMS can up-regulate the level of p-AKT while knocking down SMS can reduce the expression of p-AKT ( Figure 3C ).…”
Section: Resultssupporting
confidence: 74%
“…It should be realized that SMS may also directly act on other oncogenes through protein-protein interactions. There are three domains in SMS protein ( 29 , 30 ). By searching The Molecular INTeraction Database (MINT database), we found some proteins that may interact with SMS proteins, including IMMP2L, MAPK6, MAPKAPK3, MAPK8IP2, RPS6KA3.…”
Section: Resultsmentioning
confidence: 99%
“…Gene therapy and mRNA therapy are in preclinical trials for fragile X and Rett syndrome but neither is available for clinical use (Hooper et al, 2021; Katz et al, 2012). A prodrug has been recently developed for Snyder‐Robinson syndrome (Tantak et al, 2021). Identification of the causes of XLID, however, have allowed prevention methods (carrier testing, prenatal diagnosis, preimplantation genetics, donor gametes) to be used by couples at risk of recurrence in their offspring.…”
Section: Medical Carementioning
confidence: 99%
“…Antioxidant treatment, such as the ROS scavenger AD4, partially restores mitochondrial function but not lysosomal function in the Drosophila model ( 22 ). Certain polyamine analogs also show some benefit in rebalancing the spermidine/spermine ratio in cell lines and disease models ( 28 , 29 ). Efforts to rebalance the spermidine/spermine ratio by direct spermine supplementation in vivo have not been beneficial ( 28 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Certain polyamine analogs also show some benefit in rebalancing the spermidine/ spermine ratio in cell lines and disease models (28,29). Efforts to rebalance the spermidine/spermine ratio by direct spermine supplementation in vivo have not been beneficial (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%